Mechanisms for implementing the principles of social dialogue in the activities of the International Labour Organization (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article analyses the importance of social dialogue in the programme and standard-setting activities of the International Labour Organization. It is the only and universal international organisation that has been developing international labour standards for more than a century on the basis of full involvement of all participants in social and labour relations.Based on the analysis of the ILO’s policy documents, it has been noted that social dialogue is given a prominent place in the fundamental principles and rights at work. Social dialogue also forms the basis for the implementation of other fundamental rights. This includes the prohibition of forced labour, non-discrimination in the workplace and in social and labour relations in general, and the prohibition of the worst forms of child labour. It is emphasised that the right to freedom of association and effective recognition of the right to collective bargaining play a dual role (both as a fundamental human right in the field of labour and as an important component of social and political processes). It is proved that social dialogue as interpreted by the International Labour Organization includes all types of negotiations, consultations and information exchange between the main participants of social and labour relations. Moreover, as emphasised in the latest developments of this organisation, the importance of social dialogue is not limited to tripartite communications and improvement of social and labour relations. It is a means of ensuring social justice and a necessary condition for consolidating democratic institutions and improving democratic governance. The author substantiates the possibility of applying the category of “comprehensive mechanism for ensuring and implementing the principles of social dialogue”. Such a mechanism should consist of legal, communicative, institutional and educational and legal mechanisms. Furthermore, a comprehensive mechanism is not reduced to the sum of specific targeted mechanisms, but rather includes a set of necessary means and measures for implementing the principles of social dialogue.
Keywords: International Labour Organization; social dialogue; fundamental principles and rights in the world of work; mechanisms for implementing the principles of social dialogue.